Enrolee’s Knowledge and Satisfaction with State Health Insurance Scheme among Public School Teachers in Shomolu Local Government Area, Lagos State - Ezekiel Oridota Olufela; Oluwatosin Hannah Adepoju; Anirejuoritse Alero Chima-Oduko; Adaeze Elfrida Egwudo; Kalanne Ada Alexander; Rita Arodovwe Agunlanna (Nigerian Postgraduate Medical Journal)
Background: To bridge the coverage gap of health insurance and the delay in achieving universal health coverage, the State Health Insurance Scheme (SHIS) was established to ensure access to affordable health care for all. The scheme’s sustainability and utilisation are largely dependent on the knowledge and satisfaction of its enrolees. Aim: The study aimed to assess enrolee’s knowledge, utilisation and satisfaction with SHIS among public school teachers in Shomolu Local Government Area, Lagos State. Subjects and Methods: This was a descriptive cross-sectional study conducted among 304 public school teachers in Shomolu Local Government Area, Lagos, Nigeria using a multistage sampling method. Data were collected using pre-tested semi-structured self-administered questionnaires and analysed with EPI Info 7.2 statistical software. The level of significance was set at P < 0.05. Results: Thirty-four per cent of the respondents had good knowledge of health insurance while 66% were not familiar with the benefits and advantages. About 85.9% of the respondents have utilised the scheme and of these 51% were satisfied while 49% were not satisfied. There was a statistically significant association between out-of-pocket (OOP) and satisfaction (P = 0.0003), marital status and utilisation (P = 0.01) and OOP and utilisation (P = 0.03). Conclusion: The majority of the teachers lacked adequate knowledge of health insurance and half of them are satisfied with the services. There should be increased awareness for enrolees joining the scheme and an urgent need to improve the quality of care/services among enrolees in the scheme.